Analisis terhadap Pencegahan Tindak Pidana Pencucian Uang oleh Bank Negara Indonesia - Nugroho, Nur; Sunarmi, Sunarmi; Siregar, Mahmul; Munthe, Riswan (Universitas Medan Area, 2020)
Money laundering can undermine the national economy as it is very closely linked to the belief that one or another country against the policy of the State. Usually money laundering illicit money was made by mixing with legitimate money so that a legitimate business will not compete with companies who are honest, undermining the integrity of the financial markets due to the financial institutions (financial institutions) even rely on the proceeds of crime can face the danger of liquidity; resulting in a loss of government control of the economy of a country whose policies result in lack of confidence in other countries against its policies. In carrying out its supervisory duties USU Bank BNI has implemented Law No. 8 of 20110 on AML with Bank Indonesia Regulation No. 11/28 / PBI / by applying the principle to know the Customer and step in stages in accordance with Circular No. 11/31 / DPNP Year 2009 Standard Guidelines for the Implementation of Anti-Money Laundering and Combating the Financing of Terrorism for Banks